Research :“Perching the Vessleof Hua Hin Model for blood donation.” - จินดา ประกายพรรณ; มงคลศิริโรจน์ รุ่งอรุณ; วงศ์คำ สายทอง; บุษยพรรณพงศ์ หทัยรัตน์; จันทร์เพิ่ม ผกาวรรณ (Hua Hin Medical Journal, 2019)
The purposeof this research were to 1) develop of guidelines for blood donation in Hua Hin model 2) evaluateof guidelines for blood donation in Hua Hin modeldeveloped by mean of Research and Development (R&D)approach which composed of1. Painless while perching a needle - during donation – takeoff a needle 2. to perching a needle by determining the proper position to be able to perching a needle once one bag was drilled.Blood donors wanted to donate but can’tfind the vessel can successes perching blood once.Evaluation of Technical under the ethics of nursing . According to the conceptual framework and the achievement of a solution Symptom Management Model appears as Humphreys, J., et. al., in Smith, M.J. and Liehr, P.R. (eds., 2008) ของ UCSF School of Nursing (School of Nursing University of California, San Francisco). Implemented the model in the nurse team of blood donation 2-6 person in 28 groups.Selected the clients who had donated blood at least two times withshaped obese and can’t touch a vessel with 114 person.Studying these model in 22 dialysis for Reliability. Selected Data by Indepth Interveiw, Focus group, Logging Data analysis And the record level of pain (Numerical Rating Scale), analysis of quantitative data.Using statistic, percentage, average, mean.Qualitative data by content analysis.The findings revealed that: The development of model has 2 guideline: 1) While perching a needle, reduce pain during such service, while drilling for vein cut by placing the needle at an angle of 45 degrees to the skin - the blood flow into the bag to stick plaster is 1 inch from the bulb syringe to a needle - pull the needle out slowly by gently pulling the cable of blood bag. 2) To perching a needle by determining the proper position to be able to perching a needle once one bag was drilled at the lower center of the crook of 1.5 cm, an angle of 5 – 15 degree to the skin depth of no more than half, the length of the needle (needle length 1.5 cm). The Quality of model: 1) Client pain while perching a needle - during donation – takeoff a Needle = 0.5-1-1 2) Perching a needle once one bag and did not affect the nerves have 91.2%. To test the reliability of innovation in Dialysis unit = 90.9%. Satisfaction of the model.Including increasing the number of times a year, from 1 time to 2 – 4 times, almost all the new growth. The participants were joined by the 100% commissions and voluntary. The organizations is to increase the yield from 6.18 to 10.33 Unit. Productivity increased 67.15%